THE EFFECT OF TYPE ZEOLITE ON THE GAS TRANSPORT PROPERTIES OF POLYIMIDE-BASED MIXED MATRIX MEMBRANES - Tutuk Djoko Kusworo; Ahmad Fauzi Ismail; Azeman Mustafa; Kang Li (Reaktor, 2008)
The permeation rates of O2, N2, CO2 and CH4 has been studied for polyimide-polyethersulfone (PI/PES) blends-zeolite mixed matrix membranes synthesized in our laboratory. The study investigated the effect of zeolite loading and different zeolite type on the gas separation performance of these mixed matrix membranes. Frequency shifts and absorption intensity changes in the FTIR spectra of the PI/PES blends as compared with those of the pure polymers indicate that there is a mixing of polymer blends at the molecular level. Differential scanning calorimetry measurements of pure and PI/PES blends membranes have showed one unique glass transition temperature that supports the miscible character of the PI/PES mixture. The PI/PES-zeolite 4A mixed matrix membrane with 25 wt % zeolite loading produced the highest O2/N2 and CO2/CH4 selectivity of around 7.45 and 46.05, respectively.